Methods for molecular characterization of dissolved organic matter in the alpine water environment: an overview - Zhang, Yongbao; Du, Jianqing; Xiao, Kang (Frontiers in Environmental Chemistry, 2024)
The alpine area has become a sensitive indicator and amplifier of global climate change and human activities because of its unique geographical and climatic conditions. Being an essential part of biochemical cycling, dissolved organic matter (DOM) could effectively help understand the process, structure, and function of alpine aquatic ecosystems. Due to the low content and sampling difficulties, the analysis of DOM in alpine water demands high sensitivity with low sample volume, which has not been comprehensively reviewed. This review summarizes the DOM sampling, pretreatment, and analysis methods involving the characterization of concentration, spectroscopy, and molecular structure. Overall, conventional parameters are the basis of advanced characterization methods. Spectroscopic tests can reveal the optical properties of DOM in response to lights from ultraviolet to infrared wavelengths, to distinguish the chemical composition. Molecular structure characterizations can provide microscopic information such as functional groups, element ratios, and molecular weights. The combination of multiple methods can depict DOM composition from multiple perspectives. In sum, optimized sampling and pretreatment, high-sensitivity molecular characterization, and method integration are crucial for effectively analyzing DOM components in alpine waters. These perspectives help to standardize the DOM characterization process and to understand the correlation between DOM composition and its properties, as well as the migration and transformation of DOM.